Síndrome febril indeterminado em doente com dermatomiosite - Duarte, C (2009)
The authors present a clinical case of a male, 54 year-old with the diagnosis of Dermatomyositis has 2 months ago. The patient, after a partial response to immunosuppressive therapy, presents with Fever of unknown origin. After a deep clinical evaluation it was established the diagnosis of resistant pulmonary tuberculosis. The differential diagnosis of fever of unknown origin in patients with dermatomyositis is discussed.